The level of professional stress among public health recreational sports activity - محمد بوعزيز; بلجيلالي كمال; دحو مختار (Journal of Sport Science Technology and Physical Activities, 2024)
The study aims to identify the level of professional pressures for doctors who practice and do not ractice recreational sports activity. For this purpose, the researchers used the descriptive approach on a sample of 35 doctors who were randomly selected. To collect data, they used the occupational pressures scale. After collecting the results and treating them statistically, it was concluded that practicing doctors Recreational sports activities are characterized by low occupational pressures, while their peers who do not practice these activities are characterized by high pressures. Finally, he recommended the necessity of providing suitable facilities to practice these activities